2014
DOI: 10.1093/alcalc/agu045
|View full text |Cite
|
Sign up to set email alerts
|

Declining Trends in Alcohol Consumption Among Swedish Youth—Does the Theory of Collectivity of Drinking Cultures Apply?

Abstract: The theory of collectivity of drinking cultures seems valid for understanding changes in alcohol consumption among Swedish year 11 students. No support was found for a polarization of alcohol consumption in this nationally representative sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
71
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 19 publications
13
71
0
1
Order By: Relevance
“…Gustafsson [34, p. 464] and Bloomfield et al [35] argue that southern Sweden is now characterized by social drinking, rather than drinking to intoxication. Studies by Hallgren et al [42] and Stafström [60] found some increases for heavier-drinking youth, but their results are not supported by four other youth studies [41,58,61,59]. Figure 5 displays trends for Swiss alcohol consumption and cirrhosis mortality.…”
Section: Results For Swedenmentioning
confidence: 88%
“…Gustafsson [34, p. 464] and Bloomfield et al [35] argue that southern Sweden is now characterized by social drinking, rather than drinking to intoxication. Studies by Hallgren et al [42] and Stafström [60] found some increases for heavier-drinking youth, but their results are not supported by four other youth studies [41,58,61,59]. Figure 5 displays trends for Swiss alcohol consumption and cirrhosis mortality.…”
Section: Results For Swedenmentioning
confidence: 88%
“…Diverging trends in adolescent and adult alcohol consumption have been observed in several European countries (Raninen, Livingston & Leifman 2014;Meng et al 2014), Norway included (Brunborg, Bye & Rossow 2014). The increase in consumption peaked earlier and has been declining at a faster rate in the adolescent population than among adults.…”
Section: Alcohol and Adolescencementioning
confidence: 96%
“…It is often seen as a way to exhibit social maturity and represent a way for adolescents to experiment with identities (Johnson 2013;Demant & Järvinen 2006;Demant & Østergaard 2007). While abstention rates have been increasing in recent birth cohorts, both in Europe and internationally (Livingston 2014;Meng et al 2014;Raninen, Livingston & Leifman 2014), discourse analysis show that drinking alcohol is still viewed as the norm by young people (Hepworth et al 2016). …”
Section: Alcohol and Adolescencementioning
confidence: 99%
“…In 2012, the total alcohol consumption had decreased to about 9 liters of pure alcohol per inhabitant over 15 years of age (The Swedish Council for Information on Alcohol and Other Drugs, 2012;Ramstedt, 2013). The consumption is skewed, with about 10% of consumers accounting for about half of the alcohol intake (Mustonen et al, 2007;Raninen et al, 2014). Also, women drink about half the amount of men (Helmersson-Bergmark, 2001;Ramstedt, 2010).…”
Section: Alcohol Consumption In Swedenmentioning
confidence: 99%
“…Also, women drink about half the amount of men (Helmersson-Bergmark, 2001;Ramstedt, 2010). During the 20 th century, there has been an increase in the share of young women who report being abstainers (Raninen et al, 2014). However, four out of five girls in year 11 (aged about 18 years) have tried alcohol at least once, and almost one third of women aged 16-29 years report having been involved in …”
Section: Alcohol Consumption In Swedenmentioning
confidence: 99%